Comparison Analysis Of Financial Performance At Pt Arkha Jayanti Persada Tbk And PT Atmindo Tbk Period 2017 – 2020 - Ismawardhani, Mutiara; Azis, Azolla Degita; Yudhawati, Diah; Masruri, M. Anwar (Jurnal HARMONI: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to analyze the comparison of the financial performance of PT Arkha Jayanti Persada Tbk and PT Atmindo Tbk which are listed on the Indonesia Stock Exchange . The data analysis method used in this study is a descriptive approach. The variables use to measure and analyze the company’s financial ratios are Liquidity Ratios (Current ratio and Quick Ratio), Solvency Ratios ( DAR and DER ), Profitability Ratios ( ROA and ROI ), and the Activity Ratio ( TATO and ITO ) for four years, 2017 to 2020. The source of the data used is financial data obtained from the Indonesia Stock Exchange. Based on the research conducted, it can be seen that the results of the overall financial ratios of PT Atmindo Tbk have a better financial performance rating compared to PT Arkha Jayanti Persada Tbk